Reactions to mistakes as a function of perfectionism and situation criticality in curling - Lizmore, M. R.; Dunn, J. G. H.; Dunn, J. C. (International Journal of Sport Psychology, 2016)
This study assessed the degree to which healthy and unhealthy perfectionists responded with different levels of anger, dejection, self-confidence, and optimism following mistakes in low- and high-criticality situations in competitive curling. A total of 343 athletes (M age = 30.78 years) completed measures of perfectionism, anger, dejection, self-confidence, and optimism in sport. Cluster analyses conducted on perfectionism responses produced three clusters - labelled healthy perfectionists, unhealthy perfectionists, and non-perfectionists - that mirrored a tripartite conceptualization of perfectionism (Stoeber & Otto, 2006). Regardless of situation criticality, healthy perfectionists reported lower anger/dejection and higher confidence/ optimism following mistakes than unhealthy perfectionists (ps < .005). Regardless of perfectionism, athletes reported lower anger/dejection and higher confidence/optimism following mistakes in low- as opposed to high-criticality situations (ps < .001). It is recommended that future research should involve the examination of both personality and situational factors when assessing athletes` emotional and cognitive reactions to mistakes in competition.